Material quality of life of street vendors during COVID-19 in Huancayo markets - Adauto De La Cruz, Sheyla Kelia (2025)
Material quality of life is the perceived level of well-being in relation to material conditions (economic, educational, health, housing, and food). The presence of street vendors is a very common phenomenon around Huancayo markets. At the beginning of the quarantine imposed by the Peruvian government due to COVID-19, informal employment increased by 74.3%. COVID-19 has disrupted the normal functioning of various sectors, including the informal sector, such as street vendors, who have been most affected. Therefore, this article aims to describe the material quality of life experienced by street vendors in the markets of Huancayo during the COVID-19 pandemic. The methodology is a basic, descriptive, quantitative study with a non-experimental, cross-sectional design. The technique used was a survey, and the instrument used was a questionnaire for 565 street vendors in Huancayo markets during the COVID-19 pandemic. The results show that their basic needs are not fully and uniformly. It is concluded that the material or objective quality of life of street vendors in Huancayo markets during the COVID-19 pandemic is deficient in the following areas: education, health, housing, and income due to the lockdown.